Regulating the Power Sector and Stemming the Tide of Crisis in Sub-Saharan Africa through Purposive Infrastructural Projects and Liberalised Electricity Policy Reforms - Ojo, Aderonke Abimbola; Ayo, Tosin Ezekiel (European Journal of Science, Innovation and Technology, 2023)
This paper examines the regulation for the power and energy sectors in sub-Saharan Africa through the emplacement of a liberalised market policy. It sought to critically examine the delineation of energy crisis or energy shortage in sub-Saharan Africa, whilst interrogating whether or not having a robust energy mix was a panacea for resolving the energy crisis in Nigeria and indeed Africa. It sought to discover the regional strategic national energy policies that can be established to resolve energy crisis in sub-Saharan Africa and the regulatory reforms that can be introduced to stimulate private investments in energy infrastructure in the region, including the legal and regulatory framework for the introduction of decentralised energy options in sub-Saharan Africa and the lessons that can be gleaned from the European Union’s liberalised electricity market in constructing a competent legal and regulatory framework to stimulate private investments in energy infrastructures in sub-Saharan Africa. The study concluded by contributing elaborately to the discussion on the importance of privatising and liberalising the power sector of sub-Saharan African countries from a legal perspective and critically examining the importance of decentralisation and diversification of energy sources in the region with a view to establishing how they are capable of enhancing infrastructure investments in the region’s power sector in light of the EU experience with two most important mechanisms of liberalisation, namely unbundling and open access as it relates to the power sector of the sub-Saharan region.